Magic universe : a grand tour of modern science - Calder, Nigel (Oxford University Press, 2005)
As a prolific author, BBC commentator and magazine editor, Nigel Calder has spent a lifetime spotting and explaining the big discoveries in all branches of science. In 'Magic Universe', he draws on his vast experience to offer readers a lively, far-reaching look at modern science.